Festschrift in honour of Dr. Roger Keith - McAlister, Vivian (Can J Surg, 2017)
The festschrift in honour of Dr. Roger Keith, past editor of the Canadian Journal of Surgery, includes essays (available at canjsurg.ca), written from a personal perspective, on the development of specialty surgery in Canada (Richard Nason, Michael Marcaccio, Michael Kelly and Lissa Peeling), evolution of the certification examination (Ward Davies), building of a megahospital (Gerald Fried) and on the changes in surgical education (Edward Davies, Christopher DeGara, E. Christopher Ellison, Richard Prinz and William Pollett), as well as personal reflections (Andrew Warshaw, Stewart Hamilton).